Vegetable choline in feed for Nile tilapia (Oreochromis niloticus) raised in a biofloc technology system (BFT): Biofloc composition, chemical composition, and fatty acid profiles in meat - Sousa A.A.* (2021)
© 2021The objective of this study was to determine whether supplementation with vegetable choline (VC: 0, 400, 800, and 1200 mg kg−1 of feed) in feed for Nile tilapia (Oreochromis niloticus) raised in a biofloc system would promote changes in fatty acid (FA) profiles in the meat. We characterized the composition of the biofloc; that is, we evaluated the meat's chemical composition and FA profiles. Concerning proximate meat composition, moisture was significantly lower in the group fed 1200 mg kg−1 of VC when compared to those of other treatments. Lipid levels were significantly higher in treatments with 800 and 1200 mg kg−1 than in the control (0 mg kg−1). The total saturated fatty acids (SFA) in meat were significantly lower in the 400 mg kg−1 treatment than in the control treatment, while they were significantly higher in the 1200 mg kg−1 treatment when compared to the control treatment. Total monounsaturated fatty acids (MUFA) in meat were significantly lower in the 1200 mg kg−1 treatment than in the control treatment. Finally, total polyunsaturated fatty acids (PUFA) in meat were significantly higher in treatments with 800 and 1200 mg kg−1 than in the control treatment. Taken together, the data suggest that supplementation of VC in diets for Nile tilapia in biofloc treatment improved FA profiles of the meat. Levels of 400 and 800 mg kg−1 of diet led a decreased SFAs and increased PUFAs (mainly DHA) and MUFAs in the meat of tilapia, all of which desirable effects from the standpoint of the consumer.